Role of biomarkers in the diagnosis of bacterial infections in rheumatic diseases - B. S. Belov; G. M. Tarasova; N. V. Muravyeva (Научно-практическая ревматология, 2019)
In modern rheumatology, the problem of differential diagnosis of bacterial infection and active rheumatic process still retains its relevance. At the same time, it is very important to search for a biomarker - the gold standard for the diagnosis of an infection in patients with rheumatic diseases (RDs) in order to rapidly determine a treatment policy. This review analyzes the diagnostic significance and possibility of using some laboratory markers for bacterial infections in modern rheumatology. It emphasizes the importance of a multimarker approach that allows increasing the significance of individual parameters in the diagnosis of infections in RD.